Record of Nycteola asiatica (Kroulikovsky, 1904) (Lepidoptera, Nolidae, Sarrothripinae) Infesting Populus deltoides in Kashmir Valley, India - Bhat, Deen Mohd.; Khan, Sajad Ahmad; Lone, Inayat Ullah (Indian Forester, 2024)
No Abstract.